Prospective, multicenter, Turkish out-of-hospital cardiac arrest study: TROHCA - EFEOĞLU, MELİS (My University, 2024)
OBJECTIVES: There is no sufficient data to provide a clear picture of out-of-hospital cardiac arrest (OHCA) across Türkiye. This study is the first to present the prognostic outcomes of OHCA cases and the factors associated with these outcomes. MATERIALS AND METHODS: The study was conducted in a prospective, observational, multicenter design under the leadership of the Emergency Medicine Association of Turkey Resuscitation Study Group. OHCA cases aged 18 years and over who were admitted to 28 centers from Türkiye were included in the study. Survived event, return of spontaneous circulation (ROSC), survival to hospital discharge, and neurological outcome at discharge were investigated as primary outcomes. RESULTS: One thousand and three patients were included in the final analysis. 61.1% of the patients were male, and the average age was 67.0 ± 15.2. Cardiopulmonary resuscitation (CPR) was performed on 86.5% of the patients in the prehospital period by emergency medical service, and bystander CPR was performed on only 2.9% by nonhealth-care providers. As a result, the survived event rate was found to be 6.9%. The survival rate upon hospital discharge was 4.4%, with 2.7% of patients achieving a good neurological outcome upon discharge. In addition, the overall ROSC and sustained ROSC rates were 45.2% and 33.4%, respectively. In the multiple logistic regression analysis, male gender, initial shockable rhythm, a shorter prehospital duration of CPR, and the lack of CPR requirement in the emergency department were determined to be independent predictors for the survival to hospital discharge. CONCLUSION: Compared to global data, survival to hospital discharge and good neurological outcome rates appear to be lower in our study. We conclude that this result is related to low bystander CPR rates. Although not the focus of this study, inadequate postresuscitative care and intensive care support should also be discussed in this regard. It is obvious that this issue should be carefully addressed through political moves in the health and social fields. Keywords: Bystander cardiopulmonary resuscitation, cardiopulmonary resuscitation, cardiopulmonary resuscitation, out-of-hospital cardiac arrest, registry, return of spontaneous circulation, survival, survived event, Turkey, Türkiye
Keywords: Tıp; Cerrahi Tıp Bilimleri; Acil Tıp; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Emergency Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; ACİL TIP; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; EMERGENCY MEDICINE; Acil Tıp Hizmetleri; Cerrahi; Emergency Medical Services; Surgery; Bystander cardiopulmonary resuscitation; cardiopulmonary resuscitation; out-of-hospital cardiac arrest; registry; return of spontaneous circulation; survival; survived event; Turkey; Türkiye